Development of Interactive Edugame Learning Media Based on Quartet Cards on Material on Changes in the State of Matter - Purwaningsih, Ratna Chandra; Andriani, Aldina Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Teachers have not been optimal in varying interactive and concrete Edugame-based technology learning media. This study aims to describe the development design and test the feasibility and effectiveness of Quartet Card-based Interactive Edugame learning media for grade IV students of SDN Pesantren, Semarang City. This type of research is Research and Development (RnD) with the Borg and Gall model. The subjects of the study were 30 grade IV students of SDN Pesantren. Data collection techniques used tests (pretest and posttest) and non-tests (observation, interviews, questionnaires and document data). Data analysis techniques used normality tests, t-tests, and N-Gain tests. The results of the study showed: (1) Quartet Card-based Interactive Edugame Learning Media was developed using the Canva application with Kuartet Card box components, instructions for using Kuartet Cards containing the competencies achieved, main cards inserted with barcodes and modified cards in the form of boom cards containing questions as rewards and punishments; (2) The results of the feasibility of the material experts were 92.5%, media experts were 90%, teacher responses were 100% and student responses were 100% in the very feasible category; (3) The effectiveness of the Quartet Card-based Interactive Edugame learning media was shown by an increase in pretest and posttest results of 36.79%, supported by the results of the paired sample t-test with a sig. value. (2-tailed) <0.001<0.05, which means there is a significant difference, and the results of the N-Gain test were 0.778 in the high category. The conclusion of this study shows that the Quartet Card-based Interactive Edugame learning media was successfully developed, feasible, and effective in improving the learning outcomes of class IV students of SDN Pesantren Semarang City on the material of changes in the state of matter.